2011
DOI: 10.1177/159101991101700106
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization Rates after Endovascular Coil Embolization in a Cohort of Matched Ruptured and Unruptured Cerebral Aneurysms

Abstract: The aim of this study was to retrospectively assess the recanalization rate, factors associated with and time taken for recanalization to occur in a matched ruptured and unruptured aneurysm population that were treated with endovascular coiling. Ruptured and unruptured aneurysms treated between 2002 and 2007 were matched for aneurysm location, diameter and neck size. Recanalization rate, time to recanalize, re-treatment rate and clinical outcome were analysed. Ninet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…As in several series, the occurrence of post-embolization recanalization was more frequent in the group of patients with ruptured aneurysms [33,34]. The rate of late recanalization after embolization seems to be comparable to other large series reported in the literature [35,36].…”
Section: Angiographic Outcomesupporting
confidence: 65%
“…As in several series, the occurrence of post-embolization recanalization was more frequent in the group of patients with ruptured aneurysms [33,34]. The rate of late recanalization after embolization seems to be comparable to other large series reported in the literature [35,36].…”
Section: Angiographic Outcomesupporting
confidence: 65%
“…The present study identified greater aneurysm volume, PD less than 31% and initial occlusion Class of IIIb to be associated with treatment failure. There have been a number of previous studies designed to identify the factors associated with incomplete aneurysm occlusion and recurrence (Table 6) [5][6][7][8][9][10][11][12][13][14]. The list of factors associated with recurrence include SAH, younger age, aneurysm dome size, aneurysm neck diameter, aneurysm location, aneurysm multiplicity, PD, incomplete aneurysm occlusion and duration of follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have identified larger aneurysm size to be a predictor of incomplete aneurysm occlusion and recurrence [4,7,[9][10][11][12][13][14]. Aneurysm diameter greater than 10 mm [4,10,11] and neck diameter greater than 4 mm [10,11,13] are two cut-off points that have been repeatedly shown to be associated with recurrence.…”
Section: Aneurysm Sizementioning
confidence: 97%
See 1 more Smart Citation
“…Recurrence after endovascular coiling was reported to be associated with aneurysm dome size. 15,23,28) Follow-up angiographic results after complete aneurysm embolization showed recurrence rates of 14% for aneurysms º5 mm, 27% for those 5-10 mm, and 57% for those À10 mm. 28) Therefore, the lower rate of recurrence in our series may be attributable to the lower proportion of cases with aneurysms AE5 mm.…”
Section: Discussionmentioning
confidence: 99%